2021
DOI: 10.1038/s41467-021-25735-9
|View full text |Cite
|
Sign up to set email alerts
|

A rational blueprint for the design of chemically-controlled protein switches

Abstract: Small-molecule responsive protein switches are crucial components to control synthetic cellular activities. However, the repertoire of small-molecule protein switches is insufficient for many applications, including those in the translational spaces, where properties such as safety, immunogenicity, drug half-life, and drug side-effects are critical. Here, we present a computational protein design strategy to repurpose drug-inhibited protein-protein interactions as OFF- and ON-switches. The designed binders and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…Previously, we reported that known peptide inhibitors, mimicking a variety EL1 or EL2 sequences of Cx43 subtype, appear non-selective when binding to Cx43 versus Cx36 GJC subtypes [ 15 ]. In searching for potentially Cx subtype-specific inhibitors, we devised a strategy to design protein components and/or small molecules involved in the inhibition of protein-protein interactions [ 16 , 17 , 18 ]. Here we explore the prospective approach to inhibit connexon coupling by targeting distinguishable Cx subype-specific structural motifs within the GJ domain.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that known peptide inhibitors, mimicking a variety EL1 or EL2 sequences of Cx43 subtype, appear non-selective when binding to Cx43 versus Cx36 GJC subtypes [ 15 ]. In searching for potentially Cx subtype-specific inhibitors, we devised a strategy to design protein components and/or small molecules involved in the inhibition of protein-protein interactions [ 16 , 17 , 18 ]. Here we explore the prospective approach to inhibit connexon coupling by targeting distinguishable Cx subype-specific structural motifs within the GJ domain.…”
Section: Introductionmentioning
confidence: 99%
“…37,39,[85][86][87] Moreover, because our designed peptides and protein assemble efficiently in cells, such as E. coli, we anticipate applications to intervene in and to augment natural sub-cellular processes. 10,53,58,62,88,89 In short, we believe that our work adds fundamental understanding of the structural principles and sequence-to-structure relationships for coiled coils generally and 4-helix bundles specifically; and that our new designs provide platforms for future de novo design, and chemical and synthetic biology programs.…”
Section: Discussionmentioning
confidence: 86%
“…37, 39, 8587 Moreover, because our designed peptides and protein assemble efficiently in cells, such as E. coli , we anticipate applications to intervene in and to augment natural sub-cellular processes. 10, 53, 58, 62, 88, 89…”
Section: Discussionmentioning
confidence: 99%
“…37,39,[85][86][87] Moreover, because our designed peptides and protein assemble efficiently in cells, such as E. coli, we anticipate applications to intervene in and to augment natural subcellular processes. 10,53,58,62,88,89 In short, we posit that our work adds fundamental understanding of the structural principles and sequence-to-structure relationships for coiled coils generally and 4-helix bundles specically; and that our new designs provide platforms for future de novo design, and chemical and synthetic biology programs.…”
Section: Discussionmentioning
confidence: 96%